PDMS-based self-replenishing coatings. (19th December 2016) - Zhang, Y.; Karasu, F.; Rocco, C.; van der Ven, L.G.J.; van Benthem, R.A.T.M.; Allonas, X.; Croutxé-Barghorn, C.; Esteves, A.C.C.; de With, G.
Abstract: For the first time, we report the use of PDMS low surface energy blocks to build self-replenishing hydrophobic coatings. As the use of 8-fluorinated-carbon (Teflon-like) end groups (Rf8 ) has been perceived as a serious concern in industry due to its potential harm for health and environment, alternatives are sought. Poly(dimethyl siloxanes) (PDMS) have become an attractive eco-friendly alternative as low surface energy building blocks for self-replenishing surfaces with low environmental impact. Hence, new coating systems with PDMS-based chain ends were investigated. Following the design criteria for self-replenishing coatings, several important aspects have been characterized, such as network flexibility, dangling chains surface segregation and surface reorganization ability. After demonstrating that all the design criteria have been met, the self-replenishing behavior after intentional damage was examined via characterizations with water contact angle and XPS measurements. Based on the results, we conclude that the chemical composition at the damaged surfaces was recovered with a clear PDMS enrichment, but that the hydrophobicity recovery is dependent on the environmental temperature. This extraordinary temperature dependence seems to be due to the hindrance on full reorientation of the dangling chains by the PCL spacer crystals formed at the air interface. The effect of PDMS block molecular mass M w and PCL spacer length are discussed in terms of surface segregation, reorganization and self-replenishing behavior. Graphical abstract: Highlights: PDMS low-surface-energy blocks to build self-replenishing hydrophobic coatings. PDMS acting as attractive eco-friendly alternative for low surface energy coatings. Study of network flexibility, dangling chains segregation and surface reorganization. Characterization of initial and damaged surfaces with water CA and XPS.